2013
DOI: 10.1007/s11695-013-1062-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Staple-Line Leak in Sleeve Gastrectomy: Reinforcement with Bovine Pericardium vs Oversewing

Abstract: One of the most serious, potentially life-threatening complications of laparoscopic sleeve gastrectomy (LSG) is staple-line leakage. Oversewing the LSG staple line vs buttressing it with bovine pericardial strips (BPS) to reduce perioperative bleeding and postoperative gastric leak was evaluated. From 2006 through 2011, 160 patients underwent LSG with suturing as the only staple-line reinforcement (Group A). From March 2010 through August 2012, 84 LSG patients had BPS incorporated into their last two stapler f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…The use of bovine pericardium strips has been shown to reduce staple-line bleeding, with fewer days of hospitalization compared with patients with no staple-line reinforcement [14]. Recently, Hajj et al 2013 reported that bovine pericardium strips were associated with a lower staple-line leak rate compared with over-sewing [19]. PSD-V, approved in the USA, has received the CE Mark (indicating product compliance with European Union legislation) and has recently been approved in India.…”
Section: Introductionmentioning
confidence: 99%
“…The use of bovine pericardium strips has been shown to reduce staple-line bleeding, with fewer days of hospitalization compared with patients with no staple-line reinforcement [14]. Recently, Hajj et al 2013 reported that bovine pericardium strips were associated with a lower staple-line leak rate compared with over-sewing [19]. PSD-V, approved in the USA, has received the CE Mark (indicating product compliance with European Union legislation) and has recently been approved in India.…”
Section: Introductionmentioning
confidence: 99%
“…Three meta-analyses and several systematic reviews have been published within the past 5 years on the use of staple line reinforcement with varying conclusions ranging from no significant effect on bleeding or leak, variable effect on leak depending on the material used for buttressing without assessment of bleeding and no effect on leak but decreased staple line bleeding. One review identified buttressing to be associated with an increased risk of bleeding [67][68][69][70][71][72][73][74][75][76]. There is one randomized controlled trial on the use of fibrin sealant during SG that reported a significant reduction in operative bleeding, although the clinical relevancy of this finding was not clear.…”
Section: Prevention Of Gi Leaks After Sgmentioning
confidence: 99%
“…Leak incidence, however, was not found to be significantly different [77]. Most studies have not shown over-sewing to reduce the incidence of leak [67,78,79]. The heterogeneity of the studies, small statistical power, discrepancy of buttressing materials utilized and over-sewing methods in conjunction with varying staple heights and techniques (different bougie sizes) limit any recommendations regarding the use of these materials to prevent GI leak after SG.…”
Section: Prevention Of Gi Leaks After Sgmentioning
confidence: 99%
“…BPS has additionally been associated not only with decreased leak and bleeding rates but also with increased complications such as gastric fistula and infection [16][17][18]. Small prospective cohort studies comparing SLR techniques in LSG have found no significant difference in complication rates, but lack sufficient power [3,19,20]. A recent systematic review comparing APM, BPS, oversewing, and no reinforcement demonstrated that the leak rate in LSG was lowest with the use of APM [8], but this contrasted with a multi-institutional study that demonstrated the lowest leak rate with BPS [21].…”
Section: Introductionmentioning
confidence: 99%